-3(3s-4)-12=-2(8s+10)-2

Simple and best practice solution for -3(3s-4)-12=-2(8s+10)-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(3s-4)-12=-2(8s+10)-2 equation:


Simplifying
-3(3s + -4) + -12 = -2(8s + 10) + -2

Reorder the terms:
-3(-4 + 3s) + -12 = -2(8s + 10) + -2
(-4 * -3 + 3s * -3) + -12 = -2(8s + 10) + -2
(12 + -9s) + -12 = -2(8s + 10) + -2

Reorder the terms:
12 + -12 + -9s = -2(8s + 10) + -2

Combine like terms: 12 + -12 = 0
0 + -9s = -2(8s + 10) + -2
-9s = -2(8s + 10) + -2

Reorder the terms:
-9s = -2(10 + 8s) + -2
-9s = (10 * -2 + 8s * -2) + -2
-9s = (-20 + -16s) + -2

Reorder the terms:
-9s = -20 + -2 + -16s

Combine like terms: -20 + -2 = -22
-9s = -22 + -16s

Solving
-9s = -22 + -16s

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '16s' to each side of the equation.
-9s + 16s = -22 + -16s + 16s

Combine like terms: -9s + 16s = 7s
7s = -22 + -16s + 16s

Combine like terms: -16s + 16s = 0
7s = -22 + 0
7s = -22

Divide each side by '7'.
s = -3.142857143

Simplifying
s = -3.142857143

See similar equations:

| (4x-5)(2x-3)= | | 5x+5=(x-23) | | -18t^4+9t^3+2t= | | .6w-.3w+.2w=3 | | 7y-9y=16 | | 15x-23x=1/3 | | (10b-3)-3(3b+1)=-6 | | f(x)=-7*x^2+5*x+7 | | -2x-10=6x+30-12 | | 2k+6=8k-20+38 | | y=-3/5+3 | | -3/5+3 | | 16=10+32x-16x^2 | | 1454-16x^2=0 | | (x+1)(x+9)-(x-3)(x+5)= | | 1/4x+5/4=9 | | -2.7x^2+35x-3=0 | | 6x+20=8x+4 | | -2.7x^2+35x+3=0 | | 3x+33y=-24 | | 5x+19=8x+7 | | 9+16/4+5*6 | | 19+5-8*4/2 | | 9/10+y/7 | | 9/10+y/1 | | 24/12+5*7 | | -25/8*64/9 | | b/a=15 | | -4(-4v-u)-5(-6u+3v)= | | -31/8*71/9 | | 3t-10=-20/t | | yz=20 |

Equations solver categories